Photoinduced isomerization of the photoactive yellow protein (PYP) chromophore: interplay of two torsions, a HOOP mode and hydrogen Bonding - Gromov, Evgeniy; Burghardt, Irene; Köppel, Horst; Cederbaum, Lorenz S. (The journal of physical chemistry. A, Molecules, clusters, and aerosols, 2011)
We report on a detailed theoretical analysis, based on extensive ab initio calculations at the CC2 level, of the S1 potential energy surface (PES) of the photoactive yellow protein (PYP) chromophore. The chromophore’s photoisomerization pathway is shown to be fairly complex, involving an intimate coupling between single-bond and double-bond torsions. Furthermore, these torsional modes are shown to couple to a third coordinate of hydrogen out-of-plane (HOOP) type whose role in the isomerization is here identified for the first time. In addition, it is demonstrated that hydrogen bonding at the phenolate moiety of the chromophore can hinder the single-bond torsion and thus facilitates double-bond isomerization. These results suggest that the interplay between intramolecular factors and H-bonding determines the isomerization in native PYP.
Gesehen am 11.07.2022